Himmelwärts / Das unbekannte Leben / Mit dem Kopf durch die Wand - Streitler-Kastberger, Nicole (Wiener Ausgabe sämtlicher Werke, 2020)
This volume presents two lesser-known plays from Horváth's middle creative period - the tragicomedy Skyward, which he titled a "fairy tale," and the comedy Head On. The volume reconstructs the plays' writing process. Especially in the case of Head On, it becomes clear how intensely Horváth worked on polishing the text, which survives in three different final versions.